Kebijakan Pendidikan Islam Berbasis Motto Daerah “Bersujud” di Kabupaten Tanah Bumbu Kalimantan Selatan - Rusdiansyah, Rusdiansyah (SYAMIL: Journal of Islamic Education, 2020)
The presence of a motto is not just a word sweetener. But it must have meaning that can be implemented in a concrete form. The values of Islamic education contained in the prostration motto can be implemented in the form of policies by the government as the formulator of the motto. So, it becomes a necessity if the motto "prostrate" is applied by the community, it will be able to bring to the regional development goals. This study aims to describe the policy of Islamic education based on the prostration motto in Tanah Bumbu Regency, as well as the obstacles and carrying capacity of the government in implementing Islamic education policy based on the prostration area motto. The method used by researchers is descriptive qualitative research with a policy study approach. Collecting data with direct interview techniques to respondents, namely Dr. Zairullah Azhar Regent of Tanah Bumbu Regency for the first period (2003-2010), as well as people involved in the policy as participants and the local community as a crosscheck who felt directly the impact of the policy. The results of this study indicate that the policy of Islamic education based on the prostration area motto begins with the formulation of the concept of the prostration area motto by Dr. Zairullah Azhar, prostration is an abbreviation of the values of Islamic education that is clean, thankful, honest, and peaceful. The implementation of policies based on this prostrate values includes Divine management, the obligation to pray in congregation for the ASN (State Civil Apparatus), the midday prayer in congregation, the Al Qur'an program (before work), the Duha prayer in the morning. , grave pilgrimage as a strategy for not corruption, Islamic education in the non-formal form of recitation of the majelis ta ‟lim. However, this policy does not touch on formal institutions, and society at large. Some people's acceptance of these policies follows and some does not. Because the policy can only be felt directly by the ASN / PNS. The policy of Islamic education based on prostration motto has not been able to be implemented in general in all fields. So that finally led to a conclusion that the policy of Islamic education based on the prostrate motto has not been fully implemented properly.